Molecular and morphology identification of Squat lobster (Family Galatheidae) in Seribu Islands, Jakarta - Amanda Siregar Raissha; Putri Anggraini Nurlita; Restiana Endang Gelis Ester; Suryo Kusumo Bagus; Subhan Beginer; P Zamani Neviaty; Madduppa Hawis; Najwa Khalilah (BIO Web of Conferences)
Squat lobsters are organisms that have high abundance and can be found in almost all environmental conditions, one of which is dead coral. Due to its wide distribution and many systematic differences within the group, this group has a complex classification history. This lobster squat group can be accurately identified using molecular analysis combined with morphological identification. The purpose of this study was to identify squat lobsters on dead coral in the Seribu Islands, Jakarta through phylogenetic tree reconstruction based on molecular and morphological identification. A total of 18 squat lobster individuals collected from dead coral heads were preserved using 96% ethanol. The mitochondrial 16S rRNA gene target was used for molecular identification. The BLAST results on NCBI were identified as Allogalathea elegans, Allogalathea babai and Galathea sp. 2, which form 3 clades in the phylogenetic tree. Furthermore, we confirmed this type through morphological identification, which involves comparing the shape of the rostrum and the structure of the spines on the carapace. Both tools have been validated and can describe the types of squat lobsters in the Seribu Islands, Jakarta. Squat lobsters play a role in the food web of coral reef ecosystems as an important food source for carnivores. This study has the potential to provide insight into the function of dead coral in coral reef ecosystems and can broaden insights into marine biodiversity and also provide relevant data for the management and conservation of coral reef ecosystems.